Community Perception Towards Former Drug Convicts Participating In The Rehabilitation Program At Bentiring Prison Of Bengkulu City - Ikhsan Saputra; Octaviani, Vethy; SM, Anis Endang (Multidisciplinary Journals, 2025)
This study aims to describe the community perception of former drug convicts participating in the rehabilitation program at the Bentiring Penitentiary (Lapas) in Bengkulu City. The approach used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. Informants in this study consisted of community leaders, RT heads, and neighbors in the neighborhood where the former convicts live. The results of the study indicate that the public perception of former convicts has two stigmas, namely positive stigma and negative stigma. Some people have begun to accept and appreciate the positive changes in former convicts after rehabilitation, such as becoming more polite, working independently, and avoiding bad company. However, the negative stigma and suspicion are still quite strong, especially when social problems occur in the environment. The rehabilitation program at Bentiring Penitentiary is considered quite effective in changing behavior and providing new skills for convicts. However, the success of social reintegration is highly dependent on support from family and the surrounding environment. This study concludes that the rehabilitation program needs to be supported by public education to reduce negative stigma, as well as collaboration between the prison, government, and community in building a sustainable support system for former drug convicts.